2014
DOI: 10.1128/aac.03466-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus (HCV) NS3 Sequence Diversity and Antiviral Resistance-Associated Variant Frequency in HCV/HIV Coinfection

Abstract: HIV coinfection accelerates disease progression in chronic hepatitis C and reduces sustained antiviral responses (SVR) to interferon-based therapy. New direct-acting antivirals (DAAs) promise higher SVR rates, but the selection of preexisting resistanceassociated variants (RAVs) may lead to virologic breakthrough or relapse. Thus, pretreatment frequencies of RAVs are likely determinants of treatment outcome but typically are below levels at which the viral sequence can be accurately resolved. Moreover, it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Using a fixed cutoff can retain a large proportion of offspring sequences, introducing skewing from rerepresentation of templates with the abundant Primer ID reads as the apparent templates of offspring Primer IDs. Second, previous studies used the Roche 454 platform, which has a much lower throughput compared to the MiSeq platform used in the present study (21,24,25), which, along with the Ion Torrent platform, has a high error rate at homopolymer runs (26,27) that is not a feature of MiSeq platform. When the number of raw sequence reads per template is not sufficient (due either to low capacity or too much multiplexing), the peak of the Primer ID read distribution will be shifted toward the low-abundance error end, making template recovery significantly less than optimal (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Using a fixed cutoff can retain a large proportion of offspring sequences, introducing skewing from rerepresentation of templates with the abundant Primer ID reads as the apparent templates of offspring Primer IDs. Second, previous studies used the Roche 454 platform, which has a much lower throughput compared to the MiSeq platform used in the present study (21,24,25), which, along with the Ion Torrent platform, has a high error rate at homopolymer runs (26,27) that is not a feature of MiSeq platform. When the number of raw sequence reads per template is not sufficient (due either to low capacity or too much multiplexing), the peak of the Primer ID read distribution will be shifted toward the low-abundance error end, making template recovery significantly less than optimal (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The technology of using a degenerate block of nucleotides as indexing tags for NGS has been introduced in both DNA template sequencing (20) and RNA virus sequencing (6,21). However, adoption of this technology has been slowed by several con- cerns.…”
Section: Discussionmentioning
confidence: 99%
“…The MiSeq assay could potentially be used in cases in which the detection of minority resistance variants is important, although the performance of the assay in that context has not fully been evaluated. However, given the absence of minority variants carrying the Q80K polymorphism detected in this and previous studies (23,24) and that the population prevalence of Q80K is likely due to a founder effect rather than active selection (15), deep sequencing specifically for the NS3 Q80K polymorphism may be unnecessary.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have examined the prevalence of the Q80K polymorphism in treatment-naive and treatment-experienced populations and have demonstrated a substantial disparity in the prevalence of the Q80K polymorphism in GT1-infected populations in North America versus Europe (11,14,(21)(22)(23)(24). We have demonstrated that both Sanger sequencing of a 1,200-bp and/or 564-bp fragment of NS3 and next-generation sequencing (MiSeq) of a near-full-genome product can be used to accurately screen for the NS3 Q80K polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed with the HCV NS3 protease of genotype 1 also showed an equivalent intrasample mean pairwise nucleotide diversity, ranging from 0.0133 to 0.0174 in HCV monoinfected patients (31) (32) and between 0.0075 and 0.0120 in HCV/HIV-1-coinfected patients (18,31,33,34). A more recent study analyzed, by deep sequencing and primer ID, the HCV NS3 protease of genotype 1 from 20 HCV monoinfected patients and 20 HCV/HIV-1 coinfected patients (35). A lower intrasample mean pairwise nucleotide diversity was observed in HCV/HIV-1-coinfected patients (0.0095 Ϯ 0051) than in HCV monoinfected patients (0.0143 Ϯ 0.0069).…”
Section: Discussionmentioning
confidence: 99%